A Deep Insight into Ferroptosis in Renal Disease: Facts and Perspectives - Zhongyu Han; Yuanke Luo; Haoran Chen; Guochen Zhang; Luling You; Meiqi Zhang; Yumeng Lin; Lan Yuan; Shiyi Zhou (Karger Publishers, 2024)
Background: Ferroptosis, a newly recognized form of programmed cell death, is distinguished by its reliance on reactive oxygen species and iron-mediated lipid peroxidation, setting it apart from established types like apoptosis, cell necrosis, and autophagy. Recent studies suggest its role in exacerbating or mitigating diseases by influencing metabolic and signaling pathways in conditions such as tumors and ischemic organ damage. Evidence also links ferroptosis to various kidney diseases, prompting a review of its research status and potential breakthroughs in understanding and treating these conditions. Summary: In acute kidney disease (AKI), ferroptosis has been confirmed in animal kidneys after being induced by various factors such as renal ischemia-reperfusion and cisplatin, and glutathione peroxidase 4 (GPX4) is linked with AKI. Ferroptosis is associated with renal fibrosis in chronic kidney disease (CKD), TGF-β1 being crucial in this regard. In diabetic nephropathy (DN), high SLC7A11 and low nuclear receptor coactivator 4 (NCOA4) expressions are linked to disease progression. For polycystic kidney disease (PKD), ferroptosis promotes the disease by regulating ferroptosis in kidney tissue. Renal cell carcinoma (RCC) and lupus nephritis (LN) also have links to ferroptosis, with mtDNA and iron accumulation causing RCC and oxidative stress causing LN. Key Messages: Ferroptosis is a newly identified form of programmed cell death that is associated with various diseases. It targets metabolic and signaling pathways and has been linked to kidney diseases such as AKI, CKD, PKD, DN, LN, and clear cell RCC. Understanding its role in these diseases could lead to breakthroughs in their pathogenesis, etiology, and treatment.